The chain-mediating effects of negative physical sensation and experiential avoidance on exercise anxiety in college students - Wang, Yi; Tian, Jing; Yang, Qingxuan (Frontiers in Psychology, 2024)
Purpose: The present study aimed to explore the potential mediating role of negative physical sensation and experiential avoidance in the association between endurance exercise and exercise anxiety among university students. Method: In this study, a questionnaire method was employed to conduct the Adolescent Athlete Non-Intellectual Factors Survey Scale on 12,00 college students. From this sample, 287 individuals with exercise anxiety were identified through an endurance exercise test and the Acceptance and Action Questionnaire (AAQ-II) subsequently administered as well as The Borg Rating of Perceived Exertion (RPE). Subsequently, statistical analyses including correlation, regression, and mediation were performed using SPSS26 as the analytical tool. Additionally, the bias-corrected nonparametric percentile Bootstrap method was used to test for the mediating effects and estimate the confidence intervals with 5000 iterations, and the confidence interval (CI) was set at 95%. Finally, in AMOS24, a mediating construct was established by incorporating exercise anxiety as the dependent variable, endurance exercise behavior as the independent variable, and negative physical sensations and experiential avoidance as the mediating variables (R=0.619, R2=0.384). A path analytic procedure was employed to test the hypotheses while percentile bootstrap analysis was conducted to examine the indirect effects. Result: The results show that endurance exercise negatively predicts negative physical sensations (β=-0.48, P<0.001), negative physical sensation positively predicts experiential avoidance (β=0.36, P<0.001) and exercise anxiety (β=0.40, P<0.001), and experiential avoidance positively predicts exercise anxiety (β=0.26, P<0.001). Conclusion: There were significant correlations among endurance exercise, negative physical sensation, experiential avoidance and exercise anxiety. Endurance exercise affects exercise anxiety through two ways: 1) endurance exercise→negative physical sensation→exercise anxiety. 2)endurance exercise→negative physical sensation→experiential avoidance→exercise anxiety. Negative physical sensations and experiential avoidance play mediating and chain-mediating roles between endurance exercise and exercise anxiety.